Investigation of the static current gain for InP/InGaAs single heterojunction bipolar transistor - Jihane Ouchrif; Abdennaceur Baghdad; Aicha Sshel; Abdelmajid Badri; Abdelhakim Ballouk (Institute of Advanced Engineering and Science, 2019)
Heterojunction Bipolar Transistors are being used increasingly in communication systems due to their electrical performances. They are considered as excellent electronic devices. This paper presents an investigation of the static current gain β based on two technological parameters related to the device geometry for InP/InGaAs Single Heterojunction Bipolar Transistor (SHBT). These parameters are the base width and the emitter length . We used Silvaco’s TCAD tools to design the device structure, and to extract the static current gain β from I-V output characteristics figures. According to this investigation, we determined the optimal values of the examined parameters which allow obtaining the highest static current gain β.